2020
DOI: 10.5430/ijfr.v11n4p267
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Profitability in the Effect of Company Growth on the Debt Policy

Abstract: This study aims to examine the role of profitability as a mediating variable on the effect of company growth on debt policy. The samples were companies of textile and garment sub-sector listed on the Indonesia Stock Exchange in the 2014-2018 period. The results show that asset growth (AG) did not affect the debt to equity ratio (DER). In addition, return on asset (ROA) was found to have a positive effect on the DER. Meanwhile, the ROA could not mediate the effect of asset growth on the DER.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…The relationship between company growth and the debt to assets ratio (DAR) is complex and varies across different studies. Akhmadi et al (2020) found no significant effect of asset growth on the debt to equity ratio (DER), while (Hameed et al, 2012) reported a positive relationship between the debt to asset ratio and market to book ratio. (Sianipar, 2020) and (Syarifudin, 2021) both found a positive effect of debt to equity ratio and asset growth on dividend payout ratio and stock prices respectively.…”
Section: The Effect Of Company Growth On Debt To Assets Ratio (Dar)mentioning
confidence: 99%
“…The relationship between company growth and the debt to assets ratio (DAR) is complex and varies across different studies. Akhmadi et al (2020) found no significant effect of asset growth on the debt to equity ratio (DER), while (Hameed et al, 2012) reported a positive relationship between the debt to asset ratio and market to book ratio. (Sianipar, 2020) and (Syarifudin, 2021) both found a positive effect of debt to equity ratio and asset growth on dividend payout ratio and stock prices respectively.…”
Section: The Effect Of Company Growth On Debt To Assets Ratio (Dar)mentioning
confidence: 99%
“…This study was written to provide empirical evidence regarding the effect of SCF and financial trends on the profitability of real estate investment trusts. The findings are expected to assist policymakers and executives in real estate companies in recognizing the critical role of SCF and development finance in a company's profitability (Akhmadi et al, 2020;Suripto, 2021).…”
Section: Introductionmentioning
confidence: 95%
“…Menurut teori trade-off, ketika profitabilitas perusahaan meningkat, perusahaan akan menggunakan dana eksternal untuk mendanai operasinya untuk menarik investor. (Akhmadi et al, 2020;Novita & Ardini, 2020;Wahyuni et al, 2016) sebelumnya telah melakukan penelitian tentang profitabilitas yang berpengaruh secara positif pada kebijakan utang. Namun terdapat perbedaan dengan temuan (Irawan et al, 2016;Safitri & Wulanditya, 2017;Sha, 2018) yang semuanya menyatakan adanya pengaruh negative antara profitabilitas terhadap kebijakan utang.…”
Section: Landasan Teoriunclassified